A vertente real da nomeção: entre a representação e objeto - Barreto, Elisângela Ferreira (2013)
The investigation of this doctorate s thesis is related to the vicissitudes that lead to a psychotic individual to be able to stabilize from a nomination. Therefore, we intended to outline the field of representation concept from Aristotle, afterwards the one by Freud and his formalization about the psychic apparatus, up to Lacan and the non-representable and not-all concepts. The hypothesis, presented here, focus, essentially, on Lacan´s concept of object a and in its real function of being support of the individual s jouissance. In this research, we supposed that, in psychosis, the object a while not being extracted, it would be articulated to the nomination so as to promote the possibility of a psychic organization, with stabilization effect that could be described as possible consequences to the construction of social bond for the psychotic individual and the circumscription of the unmeasured and incommunicable jouissance that, in the psychosis, is presented as invasive and external to the individual. We are sure that the real aspect of nomination, in the psychosis, occurs from the link of the jouissance object with the name, making up a sign, not of the linguistic order, but a sign of jouissance, that would be articulated more to the field of Yade l´Um concept There is One concept extracted from Lacan´s final teaching. The name must not only nominate, but it must also be the signature of a creation, of an act, mentioning the jouissance that can not be shared. In this creative research, the individual uses their savoir-y-faire, - know how to do it because, if the extraction of the object a was not possible, it must be known how to do it where it exists.